EXPLORING FUTURE RESEARCH HORIZONS IN ARTIFICIAL INTELLIGENCE-BASED MARKETING MANAGEMENT FOR THE F&B INDUSTRY - Fitria Mumtazah (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2023)
This study examines how Artificial Intelligence (AI) is transforming the field of marketing management in the Food and Beverage (F&B) industry. By offering an understanding of AI's disruption of the traditional 4C marketing mix strategy, this research identifies challenges and threats that emerge from integrating AI into F&B marketing management. This study discovers a noticeable disassociation between marketing and the F&B supply chain, which was uncovered by VOSviewer network visualization outcomes. The visualization presents interesting avenues for future research, particularly in the field of AI-Enhanced Marketing Strategies for the F&B Industry, Integration of AI, IoT, and Industry 4.0 in the F&B Supply Chain, and Cross-Disciplinary Collaboration and Innovation. This study contributes in suggesting additional research directions for the use of AI in marketing management of the F&B industry.Penelitian ini mengeksplorasi bagaimana Artificial Intelligence (AI) mengubah kajian terkait manajemen pemasaran di industri Makanan dan Minuman (F&B). Penelitian ini juga mengidentifikasi tantangan dan ancaman yang muncul dari pengintegrasian AI ke dalam manajemen pemasaran F&B, melalui pemahaman tentang disrupsi AI terhadap strategi bauran pemasaran 4C tradisional. Hasil penelitian ini menemukan bahwa menurut hasil visualisasi jaringan VOSviewer, keterkaitan antara kajian tentang pemasaran dan F&B pada penelitian terdahulu terpisah dalam jarak yang cukup jauh. Visualisasi ini mengindikasikan peluang penelitian di masa depan, terutama di bidang strategi pemasaran berbasis AI untuk industri F&B, integrasi AI, IoT, dan Industri 4.0 dalam rantai pasokan F&B, serta kolaborasi dan inovasi lintas disiplin dalam kajian tersebut. Penelitian ini berkontribusi dalam menambahkan saran terkait arah penelitian berikutnya dalam hal penggunaan AI di bidang manajemen pemasaran industri F&B.